Convergent ecosystem responses to 23‐year ambient and manipulated warming link advancing snowmelt and shrub encroachment to transient and long‐term climate–soil carbon feedback - John Harte; Scott R. Saleska; Charlotte Levy (Global Change Biology, 2015)
Ecosystem responses to climate change can exert positive or negative feedbacks on climate, mediated in part by slow‐moving factors such as shifts in vegetation community composition. Long‐term experimental manipulations can be used to examine such ecosystem responses, but they also present another opportunity: inferring the extent to which contemporary climate change is responsible for slow changes in ecosystems under ambient conditions. Here, using 23 years of data, we document a shift from nonwoody to woody vegetation and a loss of soil carbon in ambient plots and show that these changes track previously shown similar but faster changes under experimental warming. This allows us to infer that climate change is the cause of the observed shifts in ambient vegetation and soil carbon and that the vegetation responses mediate the observed changes in soil carbon. Our findings demonstrate the realism of an experimental manipulation, allow attribution of a climate cause to observed ambient ecosystem changes, and demonstrate how a combination of long‐term study of ambient and experimental responses to warming can identify mechanistic drivers needed for realistic predictions of the conditions under which ecosystems are likely to become carbon sources or sinks over varying timescales.